Peran Literasi Keuangan Syariah Memoderasi Sikap, Norma Subjektif dan Persepsi Kontrol Perilaku Terhadap Keputusan Investasi - Amilia Agustin; Umrotul Khasanah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Indonesia's Muslim population is one of the largest in the world. This is expected to encourage the growth of the Islamic capital market, especially Generation Z which is the country's main development asset. The purpose of this study was to analyze the influence of attitudes, subjective norms and perceptions of behavioral control on the investment decisions of Generation Z investors, with Islamic financial literacy as a moderating variable. This type of research is a quantitative study involving Gen Z stock investors. The data collection technique used a purposive sampling questionnaire as a sampling method. Moderated regression analysis (MRA) and classical assumption test were used as analysis tools. The number of samples is 400 respondents. The results of the study show that the attitude variable has a significant effect on investment decisions. The subjective norm variable has no significant effect on investment decisions. The variable perceived behavioral control has a significant effect on investment decisions. And Islamic financial literacy is able to mitigate the impact of attitudes, subjective norms and perceptions of behavioral control on investment decisions. Keywords: Attitude, Subjective Norm, Perceived Behavior Control, Investment Decision, Islamic Financial Literacy